A Reassessment of the Genus Ctenoblepharis (Reptilia, Sauria, Iguanidae) with a Description of a New Subspecies of Liolaemus multimaculatus from Western Argentina - Cei, José Miguel Alfredo María (1979)
A reassessment of the heterogeneous genus Ctenoblepharis auctorum is proposed, including the species adspersus, stolzmanni, reichei and probably nigriceps. Phrynosaura Werner, 1907, and Helocephalus Philippi, 1860, are synonyms of Ctenoblepharis Tschudi, 1845; Ctenoblepharis anomalus, C. donosobarrosi, C. marmorata, C. schmidti and C. jamesi are evolutionary lines of the polymorphic genus Lioaemus. A distinct psammophilous species group is made up by Liolaemus rabinoi (Cei), Liolaemus multimaculatus multimaculatus (Dumeril and Bibron) and Liolaemus multimaculatus riojanus subsp. nov. here described. Should these lizards be accorded a formal recognition, the generic name Ortholaemus, formerly used by Girard (1857), is available. A brief discussion of the disjunct distribution of the rabinoi-multimaculatus complex is presented.